Application of silica opals to ceramic pottery. Issue 3 (2nd July 2020) - Ono, Yosuke
ABSTRACT: This paper reports the first study on using synthetic silica opals to make ceramic pottery with structural colors. The silica opals were adhered to the pottery substrate by heating at 900°C with a glass phase connecting them. The influence of the heating on the color appearance of the silica opals was investigated in depth. In the study, they were successfully adhered to the pottery substrate with no additives by using the silica opals synthesized with a small amount of catalyst reagent. This finding allows us to control iridescent/non-iridescent coloring of the silica. Additionally, we found unique color changes when the product was wetted. The detailed strategies provided in this paper for synthesizing of silica opals, coating, and heating on pottery are expected to offer useful references for the applications in the field of ceramic art.